2017
DOI: 10.1002/anie.201612516
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Octahedral Stereocenters: From Enzyme Inhibition to Asymmetric Photoredox Catalysis

Abstract: A simple concept, namely exploiting the structural and stereochemical complexity of octahedral metal complexes, can have unexpected impact in different areas of chemical research, from medicinal chemistry and chemical biology to asymmetric catalysis and photoredox chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 130 publications
0
30
0
1
Order By: Relevance
“…No separation was observed on the ion-exchange column for Na[Cu(L 1 ) 3 ] and Na[Ni(L 1 ) 3 ], pointing to the fact that geometric isomers are diastereomers and may be separated by physical means. Therefore, it is probable that such isomers may have been separated during preparation or purification [ 7 , 28 , 29 , 39 , 52 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No separation was observed on the ion-exchange column for Na[Cu(L 1 ) 3 ] and Na[Ni(L 1 ) 3 ], pointing to the fact that geometric isomers are diastereomers and may be separated by physical means. Therefore, it is probable that such isomers may have been separated during preparation or purification [ 7 , 28 , 29 , 39 , 52 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is not totally unexpected as the compounds were synthesized using asymmetric synthesis via chiral pool syntheses. Previous researches have shown that products obtained from such reactions are enantiomerically enriched in favour of the chiral starting material [ 7 , 29 , 38 , 76 ]. In the case of the glycinato complexes, the specific rotation was zero, suggestive of a racemic mixture [ 10 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Meggers and co-workers introduced octahedral iridium (III) and rhodium (III) as a new class of chiral Lewis acid catalysts. [24] The general structure of these cationic complexes is relatively simple and contains only two cyclometallated benzoxazole or benzothiazole achiral ligands in addition to the two labile coordinated acetonitriles. These complexes that exclusively display octahedral metal centrochirality (Λ or Δ) are configurationally stable (Scheme 18).…”
Section: β-Functionalization Through 14-additions (Friedel-crafts; Smentioning
confidence: 99%
“…3,4 Third-row 5d 6 iridium(III) complexes offer potential structural diversity of octahedral coordination geometry, slow ligand exchange kinetics, and facile synthesis. [5][6][7] For example, kinetically-inert octahedral iridium pyridocarbazole scaffolds can act as selective protein kinase inhibitors, 8 and inert iridium polypyridine anticancer complexes can have targets other than DNA. 9 Also, inert bis-cyclometalated iridium complexes are promising photosensitizers for singlet oxygen production, 10,11 and a diselenobenzoquinone iridium complex which targets cytochrome P450 reductase, exhibits comparable potency to cisplatin.…”
Section: Introductionmentioning
confidence: 99%